Outcomes of postnatal systemic corticosteroids administration in ventilated preterm newborns: a systematic review of randomized controlled trials - Boscarino, Giovanni; Cardilli, Viviana; Conti, Maria Giulia; Liguori, Federica; Repole, Paola; Parisi, Pasquale; Terrin, Gianluca (Frontiers in Pediatrics, 2024)
Introduction: Prolonged mechanical ventilation, commonly used to assist preterm newborns, increases the risk of developing Bronchopulmonary Dysplasia. In the last decades, studies have demonstrated a significant role of systemic corticosteroids in the prevention and management of Bronchopulmonary Dysplasia . In this systematic review of randomized controlled trials, we evaluated the association between systemic administration of corticosteroids in preterm infants and long-term outcomes including neurodevelopment, growth , extubation rate and related adverse effects. Methods: We conducted electronic searches in the MEDLINE, Scopus, and PUBMED using the terms: “premature infants” AND “corticosteroids”. We considered as eligible all randomized controlled trials published up to June 2023. All studies including preterm newborns treated with systemic corticosteroids were included. We excluded studies that evaluated inhaled corticosteroids. Results: Thirty-nine randomized controlled trials were evaluated. The influence of steroids administered systemically during the neonatal period on long-term neurological outcomes remains undefined while no influence was observed for long-term growth. The post-natal administration of systemic corticosteroids reduces the timing of extubation and improves respiratory outcomes. Dexamethasone seems to be more effective, despite a higher rate of systemic hypertension and hyperglycemia, than hydrocortisone, despite in the majority of randomized controlled trials analyzed we did not find differences in terms of adverse effects related to the post-natal corticosteroids’ administration. Conclusion: Dexamethasone administered in neonatal period seems to be more effective than hydrocortisone for respiratory outcomes however, caution should be made during administration of dexamethasone. Data deriving from current evidence, including meta-analyses, do not allow to be conclusive on the long-term effects either to exclude that there may be consequences on neurodevelopment, related to the administration of systemic steroids in preterm infants.